2015
DOI: 10.1210/en.2014-1880
|View full text |Cite
|
Sign up to set email alerts
|

Diets Containing α-Linolenic (ω3) or Oleic (ω9) Fatty Acids Rescues Obese Mice From Insulin Resistance

Abstract: Subclinical systemic inflammation is a hallmark of obesity and insulin resistance. The results obtained from a number of experimental studies suggest that targeting different components of the inflammatory machinery may result in the improvement of the metabolic phenotype. Unsaturated fatty acids exert antiinflammatory activity through several distinct mechanisms. Here, we tested the capacity of ω3 and ω9 fatty acids, directly from their food matrix, to exert antiinflammatory activity through the G protein-cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
77
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 34 publications
9
77
0
8
Order By: Relevance
“…Several studies reported that specific FA, including SFA, MUFA and linoleic acid are implicated in the development of the inflammatory process during obesity (1,2,13,14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported that specific FA, including SFA, MUFA and linoleic acid are implicated in the development of the inflammatory process during obesity (1,2,13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids (FA) are energy-rich molecules that play important physiological roles in several organs, including white adipose tissue (WAT) (1,2). In humans, the most abundant FA esterified to triglycerides are oleic (C18:1n9), palmitic (C16:0) and linoleic (C18:2n6) that account for over 85% of FA in WAT triglycerides (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors previously reported that partially replacing saturated fatty acids (SFAs) with v-3 in the diet led to reduced body fat mass, improved leptin, and better glucose sensitivity (14,15). They now show that this dietary intervention also specifically increases neurogenesis and the number of dividing cells in the arcuate and the paraventricular nuclei of the hypothalamus.…”
Section: Pencea Et Al (3) Used Brain-derived Neurotrophic Factormentioning
confidence: 99%
“…Recent studies of Velloso and colleagues (14) also have reported anti-inflammatory effects of v-3 fatty acids in both the brain and peripheral tissues, which are mediated through the actions of GPR120 and GPR40. They show that the activation of these receptors by v-3 fatty acids can reverse inflammation and insulin resistance in obese mice (15). Clinical trials focusing on pharmacological targeting of GPR40 have also demonstrated that GPR40 is capable of stimulating insulin secretion and lowering blood glucose levels (19).…”
Section: Pencea Et Al (3) Used Brain-derived Neurotrophic Factormentioning
confidence: 99%